Cotton pie production in the Semi-arid paraibano (Research, Society and Development, 2026)
This paper aims to show ways to improve the procedures for preparing cottonseeds with oil extraction for the production of cottonseed pie, highlighting each stage of the processes involved between the arrival of the cottonseeds at the agroindustry and the departure of the final products. To ensure an increase in the cottonseed pie production line, the company Raça Forte from the city of Patos - PB implemented an automated mechanical process with two work shifts (day and night), aiming to achieve a daily target of producing over 6 tons of cottonseed pie, enough to meet the demand of its buyers from several northeastern states. In addition, the efficiency of the cottonseed pie production process depends on the acquisition of some equipment required in the processes involved within the production circuit, mainly the capacity of the cooker and the number and brand of cottonseed crushing press. It is also important to highlight that at the Godefroy cotton industry in Santa Cruz de la Sierra, Bolivia, high-quality cottonseed pie has been obtained directly from the almond compared to the other two options used in Paraíba: seed and bran, especially when the aim is to increase the percentage of crude protein in the pie, it is necessary to mechanically remove the shell from the stone before pressing.